2022
DOI: 10.1177/01945998221074994
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between a Diagnosis of Anxiety or Depression and Initial VHI‐10 Scores in Benign Dysphonia

Abstract: Objective Anxiety and depression have demonstrated a positive correlation with vocal handicap among patients with benign causes of dysphonia. Our objective is to explore differences in initial Vocal Handicap Index–10 (VHI-10) scores between patients with a mental health history of anxiety or depression and those without. Study Design Retrospective cohort study. Setting Demographic data, diagnoses, and initial VHI-10 scores were collected for patients presenting with dysphonia to 2 tertiary laryngology clinics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The significance of anxiety and affective comorbidities in the field of laryngology has been mostly investigated in relation to dysphonia 4–8 . Investigations in gastroenterology, however, have suggested that psychological factors, such as anxiety or hypervigilance, may exacerbate patients' symptoms beyond any objective physiologic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The significance of anxiety and affective comorbidities in the field of laryngology has been mostly investigated in relation to dysphonia 4–8 . Investigations in gastroenterology, however, have suggested that psychological factors, such as anxiety or hypervigilance, may exacerbate patients' symptoms beyond any objective physiologic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…4 Depression has been associated with a nearly 2-fold increased chance of patients reporting voice problems. 5 Additionally, patients with a history of depression and anxiety are susceptible to developing functional voice disorders. [6][7][8] People with dysphagia often report associated anxiety and affective symptoms, as dysphagia impacts health and quality of life, notably through the disruption of the social aspect of sharing meals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sound of our own voice is a unique and familiar aspect of our self‐identity. Though the neurofunctional mechanisms of perception of one's own voice are not well understood, 1 patients with voice disorders have been shown to have significant decrement of quality‐of‐life, self‐esteem, and social function 2–7 . Studying patients' perceptions of their voices has become a valuable and actionable avenue of research within otolaryngology, and patient‐reported voice outcome measures are abundant 8 …”
Section: Introductionmentioning
confidence: 99%
“…Though the neurofunctional mechanisms of perception of one's own voice are not well understood, 1 patients with voice disorders have been shown to have significant decrement of qualityof-life, self-esteem, and social function. [2][3][4][5][6][7] Studying patients' perceptions of their voices has become a valuable and actionable avenue of research within otolaryngology, and patient-reported voice outcome measures are abundant. 8 Even among individuals without voice disorders, many report feeling uncomfortable when listening to their own voices or hearing recordings of their own voice; in these scenarios, many judge the sound of their own voice negatively.…”
Section: Introductionmentioning
confidence: 99%